Pektin Dan Potensinya Sebagai Intervensi Nutrisi Anti Kolesterol Pada Pencegahan Penyakit Kardiovaskular - Septian Aulia Najwa; Feni Rahmawati Putri; Muhammad Rifqi Aminullah (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract Cardiovascular disease remains a leading cause of mortality worldwide, with dyslipidemia, particularly elevated total cholesterol and LDL-C, as one of the most significant risk factors. This study aims to review the role of pectin, a soluble fiber from fruits and vegetables, as a non-pharmacological nutritional intervention in the prevention of cardiovascular disease. A narrative literature review was conducted using PubMed and Scopus databases, covering publications from 2020 to 2025. The findings indicate that consuming 6–15 g/day of pectin can reduce LDL levels by up to 7% without affecting HDL-C. The main mechanisms include increasing intestinal viscosity to inhibit lipid absorption, binding bile acids to enhance cholesterol excretion, and fermentation by gut microbiota to produce short-chain fatty acids (SCFAs), particularly propionate, which suppresses hepatic cholesterol synthesis. In addition, pectin improves glycemic control, insulin sensitivity, and exerts anti-inflammatory effects, contributing to overall cardiometabolic health. In conclusion, pectin shows promise as a nutritional strategy for lowering cholesterol and preventing cardiovascular disease risk, although further standardized long-term clinical studies are needed to confirm its effectiveness and consistency. Keywords: Pectin, soluble fiber, cholesterol, dyslipidemia, cardiovascular disease